Chromosome-level genome assembly and annotation of largemouth bronze gudgeon (Coreius guichenoti) - Xuemei Li; Xingbing Wu; Yongjiu Zhu; Xiaoli Li; Zihao Meng; Nian Wei; Miao Xiang; Deguo Yang; Tingbing Zhu (Scientific Data)
Abstract Coreius guichenoti, mainly distributed in upstream regions of the Yangtze River China, is currently on the brink of extinction and listed as national secondary protected animal. In this study, we aimed to obtain the chromosome-level genome of C. guichenoti using PacBio and Hi-C techniques. According to the PacBio sequencing, C. guichenoti genome was successfully assembled to 1100.1 Mb size, with a Contig N50 size of 25.0 Mb, and containing 731.0 Mb of repeats. Hi-C sequencing data was utilized for chromosome assembly and 25 chromosome sequences were ultimately yielded, with a total length of 1076.8 Mb. Moreover, a total of 22,506 protein-coding genes were predicted with average intron length of 2293 bp. Evolutionary analysis and divergence time prediction revealed that C. guichenoti was closely related to C. heterodon and they phylogenetically diverged from common ancestor ~20.7 million years ago (Mya), following the separation of Cyprinidae at 28.3 Mya. In the future, the utilization of comparative genomics research is important in elucidating the molecular mechanisms of Ichthyophthirius disease and ensuring the conservation of biological resources.